Artistic construction tools in Samrawyat's novel, Hajji Jaber - Al-Sharafat, Homedan Iqtaish Matar (Journal of Humanities & Social Sciences, 2020)
This research bears the name: (Artistic Building Tools in Samarawit Novel) by Hajji Jaber, and he addressed technical building tools as one of the technical analysis tools in stylistics, and he came in three demands: He addressed in the first requirement: the terms of study such as the technical building tools and narrative and narrative imagery, and in The second requirement: The study studied the structure of fictional speech in a novel (Samarawit), and defined the technical thresholds, and the third topic: Dealing with the tools of technical construction in the novel and the space of the novel time and space.The research has come out with some results and recommendations such as the importance of the modern stylistic study of narrative imagination, the tools of artistic construction in it, and the efforts of the narrator in transferring the story with its elements from the monotony of traditional narration to narrative imagination.
Keywords: artistic construction tools; clinical imaginary; Samrawit's novel